DEA and DSC study of cubic silsesquioxane epoxy resin nanocomposites - Diaz, N. L.; de Aquino, H. A. (European Polymer Federation, 2006)
Non-isothermal dielectric analysis (DEA) and differential scanning calorimetry (DSC) techniques were used to study the epoxy nanocomposites prepared by reacting 1,3,5,7,9,11,13,15-octa[dimethylsiloxypropylglycidylether] pentaciclo [9.5.1.1(3,9).1(5,15).1(7,13)] octasilsesquioxane (ODPG) with methylenedianiline (MDA). Loss factor (epsilon) and activation energy were calculated by DEA. The relationships between the loss factor, the activation energy, the structure of the network, and the mechanical properties were investigated. Activation energies determined by DEA and DSC, heat of polymerization, fracture toughness and tensile modulus show the same profile for mechanical properties with respect to ODPG content.